Korelasi Kegiatan Pramuka terhadap Karakter Kedisiplinan Siswa di SMA Raudlatul Ulum Kapedi - Fardan Nailul Aman; Mulyadi Mulyadi; Lilik Fadlilatin Azizah (STKIP PGRI SUMENEP, 2020)
This research aims to know the correlation of the scout activities to the discipline character of the student of SMA Raudlatul Ulum Kapedi. The kind that is used in this research is quantitative method, it is the research method that empliasizes objective measurement, numerical and the statistical analysis, so that it gives the description about the independent variable of the disciplinary character. Based on the research result at SMA Raudlatul Ulum Kapedi, it gets the result as follows, the variable of the scout activities (X) is gotten the calculated value amoun that 8,833 > t-table of 2,093. Than (8,833 > 2,093) than it is declared rejected, it means that there is the positive correlation the independent variable (scut activities) to the dependent variable (the descipline) is amounted to 81,3%. 1% addition to the value of the ability of the scout activities. So, the value of the participation increases by 1,069. So that it can be concluded that there is the correlation of the scout activities to the discipline character of the student.